Glass fiber reinforced aerated concrete and preparation process thereof

By forming an ordered nanotitanium dioxide composite layer on the surface of the glass fiber, the problem of creep deformation of aerated concrete under long-term loading conditions is solved, and its compressive strength and crack resistance are significantly improved.

CN119874310AActive Publication Date: 2025-04-25SHAANXI NEW FASHION CONSTR & INSTALLATION ENG CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510337398.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-25
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

Existing aerated concrete is prone to creep deformation of glass fibers under long-term loading conditions, resulting in a decrease in compressive strength and crack resistance.

Method used

By forming an ordered nanotitanium dioxide composite layer on the surface of the glass fiber, the creep resistance of the glass fiber is enhanced, and the pore structure of the concrete is optimized through reasonable raw material ratio and preparation process.

Benefits of technology

The compressive strength and crack resistance of aerated concrete are significantly improved. The modified glass fiber can continuously and effectively disperse stress under long-term stress, preventing stress concentration and crack expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of concrete preparation, and particularly discloses glass fiber reinforced aerated concrete and a preparation process thereof. The invention relates to glass fiber reinforced aerated concrete, which comprises the following raw materials: 20-30 parts of cement; 10 to 20 parts of fly ash; 15 to 25 parts of quick lime; 30 to 40 parts of silica sand; 0.1 to 0.3 part of aluminum powder; 0.5 to 1.5 parts of a foaming agent; 0.5-1 part of a foam stabilizer; 1-3 parts of modified glass fiber; 25 to 35 parts of water; the modified glass fiber is obtained by forming an ordered nano composite layer by nano titanium dioxide particles on the surface of the glass fiber through molecular self-assembly. According to the aerated concrete disclosed by the invention, the modified glass fibers are introduced, so that the binding power between the glass fibers and a concrete matrix is enhanced, the creep resistance of the glass fibers is also remarkably improved, and the compressive strength and the crack resistance of the aerated concrete can be effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete preparation, and more specifically, to a glass fiber reinforced aerated concrete and a preparation process thereof. Background Art

[0002] Aerated concrete is a lightweight porous silicate product made of siliceous and calcareous materials as the main raw materials, mixed with gas-generating agents, and made through processes such as batching, mixing, pouring, pre-curing, cutting, autoclaving, and curing. It is called aerated concrete because it contains a large number of uniform and fine pores after aeration. Aerated concrete has excellent thermal insulation properties. Using it to build self-insulating walls is not only convenient for construction, but also low in cost. It is a sustainable green building material that saves energy, saves land, and recycles waste. It has low production energy consumption, low construction energy consumption, and low heating energy consumption. It is the wall material with the best thermal economy.

[0003] In the related art, a Chinese patent document with announcement number CN104557107B discloses a lightweight autoclaved aerated concrete and a preparation method thereof, wherein the concrete is made of quartz sand, quicklime, cement, gypsum, and aluminum paste as the main raw materials, and inorganic fibers and grinding aids are added. The specific ratio is: 60-70 parts of quartz sand, 18-25 parts of quicklime, 9-13 parts of cement, 2-3 parts of gypsum, 0.28-0.32 parts of aluminum paste, 0.3-0.6 parts of inorganic fibers, and 3-6 parts of grinding aids. The density of the prepared concrete is 300-325kg / m³. The preparation steps are briefly described as follows: First, weigh each raw material in proportion for use. Then, add water to the quartz sand and add a grinding aid, and wet-grind with a ball mill to obtain quartz mortar. Next, the quicklime block is crushed and ground to obtain quicklime powder, and the gypsum is added with water to obtain gypsum slurry. After mixing the aluminum paste and the inorganic fiber, add water and stir evenly. After that, add quartz mortar and gypsum slurry into the pouring mixer, mix and stir while controlling the temperature, then add cement and quicklime powder and stir evenly, finally add the mixed slurry of aluminum powder paste and inorganic fiber, stir the total slurry and pour it. After pouring, pre-cure it at a certain temperature for a period of time, then demould and cut it to obtain the required specifications of the green body. Finally, the green body is cured with high temperature and high pressure steam and sampled and inspected, packaged and stored, and the finished product is obtained after natural curing. By adding a certain proportion of inorganic fibers and adjusting the preparation process, the concrete significantly improves the shrinkage rate and compressive strength of the material while ensuring the low density of the product.

[0004] In the above-mentioned technology, aerated concrete enhances compressive strength and crack resistance by adding inorganic fibers such as glass fibers. However, glass fibers are prone to creep deformation under long-term load conditions. Creep is a gradual process. Over time, glass fibers undergo continuous plastic deformation under stress. Since aerated concrete itself has a porous structure, although the pore structure can reduce the weight of the material, it also provides additional space for creep deformation of glass fibers. When glass fibers creep in these pores, their deformation degree will be aggravated by the presence of pores, which will lead to a decrease in the performance of glass fibers. Due to the accumulation of fiber deformation and performance degradation, concrete cannot effectively disperse and bear the load through the fibers when under pressure, resulting in a decrease in compressive strength. In addition, glass fibers originally play a role in enhancing and dispersing stress in concrete, which helps prevent concrete from cracking. However, creep deformation weakens this role, resulting in a decrease in the crack resistance of concrete. As creep progresses, the bonding force between the fiber and the concrete weakens, making the concrete more prone to cracks. Therefore, aerated concrete in the related art has the defects of poor compressive strength and crack resistance. Summary of the invention

[0005] In order to enhance the compressive strength and crack resistance of aerated concrete, the present application provides a glass fiber reinforced aerated concrete and a preparation process thereof.

[0006] The glass fiber reinforced aerated concrete provided in this application adopts the following technical solution: A glass fiber reinforced aerated concrete, comprising the following raw materials: 20-30 parts of cement; 10-20 parts of fly ash; 15-25 parts of quicklime; 30-40 parts of silica sand; Aluminum powder 0.1-0.3 parts; 0.5-1.5 parts of foaming agent; Foam stabilizer 0.5-1 part; 1-3 parts of modified glass fiber; 25-35 parts water; The modified glass fiber is obtained by forming an ordered nano composite layer on the surface of the glass fiber through molecular self-assembly of nano titanium dioxide particles.

[0007] By adopting the above technical solution, cement is used as the main cementitious material to provide basic strength and adhesion for concrete, and the gel structure formed by its hydration product tightly binds other raw materials. Fly ash has volcanic ash activity, which not only improves the working performance of concrete and reduces the hydration heat, but also reacts secondary with calcium hydroxide in cement hydration products in the later stage to generate more gel substances such as hydrated calcium silicate, thereby improving the durability of concrete. Quicklime and silica sand react chemically in an alkaline environment to generate products such as hydrated calcium silicate with gelling properties, further enhancing the strength of concrete. Aluminum powder, as a gas-generating agent, reacts with alkaline substances in the system to produce hydrogen, which forms a large number of evenly distributed tiny pores inside the concrete, giving aerated concrete lightweight characteristics while optimizing its thermal insulation properties.

[0008] Modified glass fiber is one of the core innovations of this application. It forms an ordered nanocomposite layer on the surface of glass fiber through molecular self-assembly of nano-titanium dioxide particles, which significantly enhances the performance of glass fiber. From a microscopic point of view, nano-titanium dioxide particles have a high specific surface area and excellent mechanical properties. When nano-titanium dioxide particles form a composite layer on the surface of glass fiber through molecular self-assembly, a variety of interactions are formed between the nano-particles and the glass fiber. On the one hand, the active groups on the surface of nano-titanium dioxide particles are connected to the groups on the surface of glass fiber through chemical bonding to form a stable chemical connection; on the other hand, there are strong intermolecular forces such as van der Waals forces between nano-particles and glass fiber. These interactions enhance the interaction between the molecular chains in the glass fiber, making it difficult for the molecular chains of the glass fiber to slip and deform when subjected to external forces, thereby effectively reducing creep deformation. In traditional aerated concrete, the reinforcing effect of glass fiber gradually weakens over time due to creep, while the modified glass fiber of this application can continuously and effectively disperse stress under long-term stress conditions by virtue of its stable nanocomposite layer structure. When aerated concrete is subjected to pressure, the modified glass fiber can evenly distribute the load throughout the concrete matrix to avoid stress concentration, thereby significantly improving the compressive strength of aerated concrete. In terms of crack resistance, the modified glass fiber can constrain the deformation of the concrete matrix. When tensile stress is generated inside the concrete, the modified glass fiber can withstand part of the tensile stress, preventing the generation and expansion of cracks, thereby enhancing the crack resistance of aerated concrete.

[0009] Optionally, the modified glass fiber is prepared by the following steps: A. Tetrabutyl titanate was added dropwise into anhydrous ethanol and mixed under magnetic stirring to form solution A; B. Mix deionized water, anhydrous ethanol and glacial acetic acid to form solution B, take solution A and solution B at a volume ratio of 1:1, and add solution B dropwise to solution A under stirring conditions. The dropping speed is controlled at 1 drop / second. After the dropping is completed, continue stirring and reacting for 1-3 hours to obtain a nano titanium dioxide sol; C. Aging, drying and calcining the nano-titanium dioxide sol to obtain nano-titanium dioxide particles; D. Adding nano-titanium dioxide particles to a toluene solution containing 3-aminopropyltrimethoxysilane, wherein the concentration of 3-aminopropyltrimethoxysilane is 0.1 mol / L, and reacting under reflux at 80° C. for 4-6 hours. After the reaction, washing with anhydrous ethanol, centrifuging and drying are performed to obtain amino-grafted nano-titanium dioxide particles. E. Sodium dodecyl sulfate, amino-grafted nano-titanium dioxide particles and aluminum triisopropoxide are mixed to obtain a reaction solution, and then the pH value of the reaction solution is adjusted to 6.5 with a dilute hydrochloric acid solution, and then glass fiber is added, and then the reaction is stirred at 40-50° C. and a speed of 200 r / min for 3-5 hours to obtain modified glass fiber.

[0010] By adopting the above technical scheme, tetrabutyl titanate is first dissolved in anhydrous ethanol to form solution A. Anhydrous ethanol can not only evenly disperse tetrabutyl titanate, but also adjust its hydrolysis rate, and form a uniform system through magnetic stirring. Deionized water, anhydrous ethanol and glacial acetic acid are mixed into solution B, and solution A is dripped at a specific speed. Deionized water participates in the hydrolysis reaction, and glacial acetic acid inhibits excessive hydrolysis, controls the formation of nano-titanium dioxide sol, and accurately controls the dripping speed and stirring time to ensure the quality of the sol. The sol is treated by aging, drying and calcination. Aging allows the particles to grow and aggregate, drying removes moisture, and calcination improves crystallinity and stability to obtain high-quality nano-titanium dioxide particles. Then, the nano-titanium dioxide particles react with 3-aminopropyltrimethoxysilane in a toluene solution, and the siloxy group condenses with the hydroxyl group on the surface of the particles, successfully grafting the amino group to provide active sites for subsequent self-assembly.

[0011] Finally, the micellar structure formed by sodium dodecyl sulfate (SDS) in the solution and aluminum triisopropoxide as a catalyst can promote the stable formation of the micellar structure of sodium dodecyl sulfate (SDS) and assist the interaction between nano-titanium dioxide particles and the surface of glass fibers. SDS forms a micellar structure in the solution, with its hydrophilic head in contact with water outward and its hydrophobic tail inward. When the glass fiber is immersed in the solution, the SDS micelles will adsorb on the surface of the glass fiber, changing the physical and chemical properties of the glass fiber surface. At the same time, the surface of the nano-titanium dioxide particles carries amino groups, and there are various intermolecular interactions with the SDS micelles and the surface of the glass fiber, such as hydrogen bonds and electrostatic effects. Under the catalytic action of aluminum triisopropoxide, these interactions are further enhanced, so that the nano-titanium dioxide particles are attracted to the vicinity of the glass fiber surface more quickly and stably. Under heating and stirring conditions, the nano-titanium dioxide particles are driven by intermolecular interactions, and the SDS micelles around the surface of the glass fiber are gradually arranged in an orderly manner. Over time, the nanoparticles and the glass fiber surface are further fixed through chemical bonding (such as the chemical bond formed after grafting with silane coupling agents) and stronger intermolecular forces, thus forming a tightly bound and well-structured nanocomposite layer. This nanocomposite layer greatly enhances the creep resistance of the glass fiber, allowing the glass fiber to better play a reinforcing role in aerated concrete.

[0012] Optionally, in step A, the volume ratio of tetrabutyl titanate to anhydrous ethanol is 1:(3-5).

[0013] By adopting the above technical solution, the above ratio ensures that tetrabutyl titanate has good solubility and dispersibility in anhydrous ethanol, while moderately controlling the hydrolysis rate, which is conducive to forming a uniform and stable sol system.

[0014] Optionally, in step B, the volume ratio of deionized water, anhydrous ethanol and glacial acetic acid is 5:(4-6):2.

[0015] By adopting the above technical solution, the above proportion control ensures the balance of hydrolysis and polycondensation reactions, and the content of glacial acetic acid effectively inhibits particle agglomeration, which helps to form a nano titanium dioxide sol with uniform particle size and stable performance.

[0016] Optionally, in step D, the mass ratio of the nano-titanium dioxide particles to the toluene solution containing 3-aminopropyltrimethoxysilane is 1:(3-5).

[0017] In the step D, the mass ratio of the nano-titanium dioxide particles to the toluene solution containing 3-aminopropyltrimethoxysilane is preferably 1:4.

[0018] By adopting the above technical solution, the above mass ratio ensures that the grafting reaction is fully carried out, so that sufficient amino groups are successfully grafted on the surface of the nano-titanium dioxide particles, providing conditions for subsequent self-assembly.

[0019] Optionally, in step E, the mass ratio of sodium dodecyl sulfate, amino-grafted nano-titanium dioxide particles and aluminum triisopropoxide is 5:10:3.

[0020] By adopting the above technical solution, the above mass ratio ensures that a uniform and dense nano-composite layer is formed on the surface of the glass fiber, thereby enhancing the creep resistance of the glass fiber.

[0021] Optionally, the foaming agent is any one of hydrogen peroxide, azodicarbonamide and sodium bicarbonate.

[0022] By adopting the above technical solution, the foaming agent can produce uniform and fine bubbles when reacting with other raw materials, optimize the pore structure of aerated concrete, cooperate with modified glass fiber, reduce the deformation of glass fiber in the pores, and improve the strength and crack resistance of aerated concrete.

[0023] Optionally, the foam stabilizer is any one of calcium stearate, sodium dodecylbenzene sulfonate and polyvinyl alcohol.

[0024] By adopting the above technical solution, the foam stabilizer can stabilize the bubbles generated during the foaming process, make the pore structure of the aerated concrete more stable, improve the stress condition of the glass fiber therein, and work synergistically with the modified glass fiber to enhance the performance of the aerated concrete.

[0025] The present application also provides a method for preparing glass fiber reinforced aerated concrete, which adopts the following technical solution: A method for preparing glass fiber reinforced aerated concrete comprises the following steps: S1. Mix the modified glass fiber with water and stir at a speed of 200 r / min for 3-5 min to obtain a fiber suspension; S2. Add cement, fly ash, quicklime, silica sand, aluminum powder, foaming agent and foam stabilizer into a mixer and stir for 3-5 minutes. Then add the fiber suspension and continue stirring for 10-15 minutes to obtain a uniform slurry. The stirring speed is 200r / min. S3. The slurry is injected into a mold and foamed at a temperature of 40-50° C. for 3-5 hours. The slurry is stirred every 30 minutes during the foaming process. After the foaming is completed, the slurry is cured to obtain glass fiber reinforced aerated concrete.

[0026] In summary, this application has the following beneficial effects: 1. This application achieves a significant improvement in the mechanical properties of aerated concrete by introducing modified glass fiber. Modified glass fiber is an ordered nano-titanium dioxide composite layer formed on the surface of glass fiber by molecular self-assembly technology. This structure not only enhances the bonding force between the glass fiber and the concrete matrix, but also significantly improves the creep resistance of the glass fiber itself. When the concrete is subjected to external forces, the modified glass fiber can effectively disperse the stress and prevent material damage caused by stress concentration. At the same time, the presence of the nano-composite layer also enhances the toughness of the glass fiber, enabling it to better constrain the deformation of the concrete matrix, thereby significantly improving the compressive strength and crack resistance of the aerated concrete. The application of this innovative technology enables aerated concrete to exhibit more excellent mechanical properties when subjected to heavy loads or complex stress environments.

[0027] 2. This application achieves the optimization of the pore structure of aerated concrete by precisely controlling the raw material ratio and preparation process. Reasonable pore distribution not only gives aerated concrete excellent properties such as light weight and thermal insulation, but also provides favorable conditions for the uniform distribution of modified glass fibers. During the preparation process, the synergistic effect of the foaming agent and the foam stabilizer causes a large number of uniform and fine bubbles to form inside the concrete. These bubbles not only improve the thermal insulation performance of the material, but also reduce the deformation and stress concentration of the glass fiber in the pores. Therefore, the optimized pore structure enables aerated concrete to significantly improve its comprehensive performance while maintaining its lightweight characteristics.

[0028] 3. The preparation process of the glass fiber reinforced aerated concrete of the present application is simple and efficient, and the cost of raw materials is controllable. During the preparation process, after the raw materials are evenly mixed in a certain proportion, aerated concrete materials with excellent performance can be obtained through simple stirring and foaming processes. In addition, the preparation process of the modified glass fiber is also relatively simple, and an ordered nanocomposite layer can be formed on the surface of the glass fiber through molecular self-assembly technology. This preparation process not only reduces production costs, but also improves production efficiency, making the material have good application prospects in the field of building materials. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Preparation example of modified glass fiber Preparation Example 1 The modified glass fiber is prepared by the following steps: A. Add 10 mL of tetrabutyl titanate dropwise into 30 mL of anhydrous ethanol, and stir at a speed of 500 r / min for 30 min under magnetic stirring to form solution A; B. Mix 5 mL of deionized water, 4 mL of anhydrous ethanol and 2 mL of glacial acetic acid to form solution B. Take 10 mL of solution A and 10 mL of solution B respectively. Add solution B dropwise to solution A under stirring at 200 r / min. The dropping speed is controlled at 1 drop / second. After the dropping is completed, continue stirring and reacting for 1 hour to obtain a nano-titanium dioxide sol. C. Aging the nano-titanium dioxide sol at 60° C. for 24 hours, then drying at 80° C. for 12 hours, and finally calcining at 500° C. for 3 hours to obtain nano-titanium dioxide particles; D. Add 10g of nano-titanium dioxide particles to 30g of toluene solution containing 3-aminopropyltrimethoxysilane (concentration of 0.1mol / L), and reflux at 80°C for 4h. After the reaction, wash with anhydrous ethanol 3 times, 10min each time, then centrifuge at 5000r / min for 5min, and then dry at 60°C for 6h to obtain amino-grafted nano-titanium dioxide particles; E. Weigh 5 g of sodium dodecyl sulfate, 10 g of amino-grafted nano-titanium dioxide particles and 3 g of aluminum triisopropoxide to obtain a reaction solution, adjust the pH value of the reaction solution to 6.5 with a dilute hydrochloric acid solution, then add 5 g of glass fiber, and then stir the reaction at 40°C at a speed of 200 r / min for 3 hours to obtain modified glass fiber.

[0031] Preparation Example 2 The modified glass fiber is prepared by the following steps: A. Add 10 mL of tetrabutyl titanate dropwise into 40 mL of anhydrous ethanol, and stir at 500 r / min for 30 min under magnetic stirring to form solution A. B. Mix 5 mL of deionized water, 5 mL of anhydrous ethanol and 2 mL of glacial acetic acid to form solution B. Take 10 mL of solution A and 10 mL of solution B respectively. Add solution B dropwise to solution A under stirring at 200 r / min. The dropping speed is controlled at 1 drop / second. After the dropping is completed, continue stirring and reacting for 2 hours to obtain a nano-titanium dioxide sol. C. Aging the nano-titanium dioxide sol at 60° C. for 24 hours, then drying at 80° C. for 12 hours, and finally calcining at 500° C. for 3 hours to obtain nano-titanium dioxide particles; D. Add 10g of nano-titanium dioxide particles to 40g of toluene solution containing 3-aminopropyltrimethoxysilane (concentration of 0.2mol / L), and reflux at 80°C for 5h. After the reaction, wash with anhydrous ethanol 3 times, 10min each time, then centrifuge at 5000r / min for 5min, and then dry at 60°C for 6h to obtain amino-grafted nano-titanium dioxide particles; E. Weigh 5 g of sodium dodecyl sulfate, 10 g of amino-grafted nano-titanium dioxide particles and 3 g of aluminum triisopropoxide to obtain a reaction solution, adjust the pH value of the reaction solution to 6.5 with a dilute hydrochloric acid solution, then add 5 g of glass fiber, and then stir the reaction at 45°C at a speed of 200 r / min for 4 hours to obtain modified glass fiber.

[0032] Preparation Example 3 The modified glass fiber is prepared by the following steps: A. Add 10 mL of tetrabutyl titanate dropwise into 50 mL of anhydrous ethanol, and stir at a speed of 500 r / min for 30 min under magnetic stirring to form solution A; B. Mix 5 mL of deionized water, 6 mL of anhydrous ethanol and 2 mL of glacial acetic acid to form solution B. Take 10 mL of solution A and 10 mL of solution B respectively. Add solution B dropwise to solution A under stirring at 200 r / min. The dropping speed is controlled at 1 drop / second. After the dropping is completed, continue stirring and reacting for 3 hours to obtain a nano-titanium dioxide sol. C. Aging the nano-titanium dioxide sol at 60° C. for 24 hours, then drying at 80° C. for 12 hours, and finally calcining at 500° C. for 3 hours to obtain nano-titanium dioxide particles; D. Add 10g of nano-titanium dioxide particles to 50g of toluene solution containing 3-aminopropyltrimethoxysilane (concentration of 0.3mol / L), and reflux at 80°C for 6h. After the reaction, wash with anhydrous ethanol 3 times, 10min each time, then centrifuge at 5000r / min for 5min, and then dry at 60°C for 6h to obtain amino-grafted nano-titanium dioxide particles; E. Weigh 5 g of sodium dodecyl sulfate, 10 g of amino-grafted nano-titanium dioxide particles and 3 g of aluminum triisopropoxide to obtain a reaction solution, adjust the pH value of the reaction solution to 6.5 with a dilute hydrochloric acid solution, then add 5 g of glass fiber, and then stir the reaction at 50° C. and 200 r / min for 5 hours to obtain modified glass fiber.

[0033] Preparation Example 4 The difference between the modified glass fiber and Preparation Example 3 is that in this Preparation Example, no aluminum triisopropoxide is added in step E. Specifically, step E is as follows: Weigh 5 g of sodium dodecyl sulfate and 10 g of amino-grafted nano-titanium dioxide particles and mix them to obtain a reaction solution. Use a dilute hydrochloric acid solution to adjust the pH value of the reaction solution to 6.5, then add 5 g of glass fiber, and then stir the reaction at 50°C and 200 r / min for 5 hours to obtain modified glass fiber.

[0034] The other steps are the same as those in Preparation Example 3.

[0035] Preparation Example 5 The modified glass fiber is different from Preparation Example 3 in that step D is not performed in this Preparation Example, that is, amino grafting is not performed on the nano-titanium dioxide particles. In the subsequent step E, the nano-titanium dioxide particles are directly used to participate in the reaction. The other preparation steps are the same as those in Preparation Example 3.

[0036] Preparation Example 6 The modified glass fiber is different from Preparation Example 3 in that the reaction solution in step E of this Preparation Example is stirred at 200 r / min for 5 hours at 30°C to obtain the modified glass fiber, and the other preparation steps are the same as Preparation Example 3.

[0037] Preparation Example 7 The modified asbestos fiber is different from Preparation Example 3 in that an equal amount of asbestos fiber is used in step E to replace glass fiber to participate in the reaction.

[0038] Example Example 1 A glass fiber reinforced aerated concrete, whose raw material components and usage are shown in Table 1, wherein the foaming agent is hydrogen peroxide; the foam stabilizer is calcium stearate, and the modified glass fiber is the modified glass fiber prepared in Preparation Example 1.

[0039] A glass fiber reinforced aerated concrete, the preparation method of which is as follows: S1, mixing the modified glass fiber with water and stirring at a speed of 200 r / min for 3 min to obtain a fiber suspension; S2. Add cement, fly ash, quicklime, silica sand, aluminum powder, foaming agent and foam stabilizer into a mixer and stir for 3 minutes. Then add the fiber suspension and continue stirring for 10 minutes to obtain a uniform slurry. The stirring speed is 200r / min.

[0040] S3. The slurry is injected into a mold and foamed at a temperature of 40° C. for 3 hours. Stirring is performed every 30 minutes during the foaming process. After the foaming is completed, the slurry is cured to obtain glass fiber reinforced aerated concrete.

[0041] Example 2 A glass fiber reinforced aerated concrete, whose raw material components and dosages are shown in Table 1, wherein azodicarbonamide is selected as the foaming agent; sodium dodecylbenzene sulfonate is selected as the foam stabilizer; and the modified glass fiber is selected from the modified glass fiber prepared in Preparation Example 2.

[0042] A glass fiber reinforced aerated concrete, the preparation method of which is as follows: S1, mixing the modified glass fiber with water and stirring at a speed of 200 r / min for 4 min to obtain a fiber suspension; S2. Add cement, fly ash, quicklime, silica sand, aluminum powder, foaming agent and foam stabilizer into a mixer and stir for 4 minutes. Then add the fiber suspension and continue stirring for 13 minutes to obtain a uniform slurry. The stirring speed is 200 r / min.

[0043] S3. The slurry is injected into a mold and foamed at a temperature of 45° C. for 4 hours. Stirring is performed every 30 minutes during the foaming process. After the foaming is completed, the slurry is cured to obtain glass fiber reinforced aerated concrete.

[0044] Example 3 A glass fiber reinforced aerated concrete, whose raw material components and usage are shown in Table 1, wherein the foaming agent is sodium bicarbonate; the foam stabilizer is polyvinyl alcohol; and the modified glass fiber is the modified glass fiber prepared in Preparation Example 3.

[0045] A glass fiber reinforced aerated concrete, the preparation method of which is as follows: S1. Mixing the modified glass fiber with water and stirring at a speed of 200 r / min for 5 min to obtain a fiber suspension; S2. Add cement, fly ash, quicklime, silica sand, aluminum powder, foaming agent and foam stabilizer into a mixer and stir for 5 minutes. Then add the fiber suspension and continue stirring for 15 minutes to obtain a uniform slurry. The stirring speed is 200r / min.

[0046] S3. The slurry is injected into a mold and foamed at a temperature of 50° C. for 5 hours. Stirring is performed every 30 minutes during the foaming process. After the foaming is completed, the slurry is cured to obtain glass fiber reinforced aerated concrete.

[0047] Table 1 Concrete components and amounts in Examples 1-3 (g)

[0048] Example 4 A glass fiber reinforced aerated concrete, which is different from Example 1 in that the modified glass fiber in this example is the modified glass fiber prepared in Preparation Example 4.

[0049] Example 5 A glass fiber reinforced aerated concrete, which is different from Example 1 in that the modified glass fiber in this example is the modified glass fiber prepared in Preparation Example 5.

[0050] Example 6 A glass fiber reinforced aerated concrete, which is different from Example 1 in that the modified glass fiber in this example is the modified glass fiber prepared in Preparation Example 6.

[0051] Comparative Example Comparative Example 1 A glass fiber reinforced aerated concrete, which is different from Example 1 in that an equal amount of unmodified glass fibers are used instead of modified glass fibers in this comparative example. Comparative Example 2 A glass fiber reinforced aerated concrete, which is different from Example 1 in that the modified asbestos fiber prepared in Preparation Example 7 is used instead of the modified glass fiber in this comparative example.

[0052] Comparative Example 3 A glass fiber reinforced aerated concrete, which is different from Example 1 in that the amount of modified glass fiber used in this comparative example is 5g.

[0053] Performance testing Compressive strength test Test object: aerated concrete prepared in Examples 1-6 and Comparative Examples 1-3.

[0054] Test method: According to GB / T11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the prepared aerated concrete is cut into 100mm×100mm×100mm cubic specimens, and cured to the specified age under the conditions of (20±2)℃ and relative humidity of (60±5)%. Then, load at a speed of (2.0±0.5) kN / s on a pressure testing machine until the specimen is destroyed. Record the failure load and calculate the compressive strength.

[0055] Test results: See Table 2.

[0056] Crack resistance test Test object: aerated concrete prepared in Examples 1-6 and Comparative Examples 1-3.

[0057] Detection method: Using the ring method, aerated concrete is made into a ring specimen with an outer diameter of 200mm, an inner diameter of 100mm, and a height of 50mm. Uniform radial tension is applied to the center of the specimen. The appearance and expansion of cracks on the surface of the specimen are monitored by a displacement sensor, and the tension value when the crack appears is recorded as an indicator of crack resistance.

[0058] Test results: See Table 2.

[0059] Table 2 Test results of Examples 1-6 and Comparative Examples 1-3

[0060] The modified glass fibers prepared using the complete process in Examples 1-3 play an effective role in aerated concrete. From the perspective of reducing creep, the nanocomposite layer on the surface of the modified glass fiber enhances the force between the molecular chains and reduces the creep deformation of the glass fiber. When aerated concrete is subjected to stress, it can continuously disperse stress, which is directly reflected in the compressive strength and crack resistance. In Example 1, because fly ash and other raw materials work well together, more hydrated calcium silicate gel is generated, the concrete structure is denser, and the modified glass fiber has a better anchoring effect therein, further inhibiting creep, and the compressive strength reaches 5.83MPa, and the crack resistance reaches 4.62kN. Although the raw material ratios in Examples 2 and 3 are changed, they still maintain high performance, indicating that raw material adjustments within a reasonable range will not affect the core role of modified glass fibers in reducing creep and enhancing performance.

[0061] In Example 4, aluminum triisopropoxide was not added when preparing the modified glass fiber. Aluminum triisopropoxide can promote the stable formation of the sodium dodecyl sulfate (SDS) micelle structure during the modification process, and assist the interaction between the nano-titanium dioxide particles and the glass fiber surface. Without aluminum triisopropoxide, the nano-composite layer is not formed perfectly, resulting in a significant reduction in the reinforcing effect of the modified glass fiber, causing the compressive strength of the aerated concrete to drop to 4.35MPa and the crack resistance to drop to 3.10kN.

[0062] In Example 5, amino grafting was not performed on the nano-titanium dioxide particles. Amino grafting is a key step to provide active sites for subsequent self-assembly. Without amino grafting, it is difficult for the nano-titanium dioxide particles to form a stable bond with the glass fiber, and the performance of the glass fiber cannot be effectively enhanced. The final compressive strength of the aerated concrete is only 3.80 MPa, and the crack resistance is 2.65 kN.

[0063] In Example 6, when preparing the modified glass fiber, the temperature of the reaction liquid in step E was 30°C, which was lower than the normal range. The lower temperature affected the orderly arrangement and chemical bonding of the nano-titanium dioxide particles on the surface of the glass fiber, making the nano-composite layer structure not tight enough, resulting in the aerated concrete compressive strength of 4.10 MPa and crack resistance of 2.80 kN.

[0064] Comparative Example 1 uses unmodified glass fiber, and no nanocomposite layer is formed, which cannot effectively strengthen concrete. Glass fiber is prone to creep under long-term stress and cannot disperse stress well, so the compressive strength is only 3.20MPa and the crack resistance is 2.20kN.

[0065] Comparative Example 2 uses modified asbestos fiber instead of modified glass fiber. Asbestos fiber itself has different characteristics from glass fiber, and is not effective in synergizing with other raw materials to enhance the performance of aerated concrete, resulting in a compressive strength of 3.00 MPa and a crack resistance of 2.00 kN.

[0066] Although modified glass fiber is used in Comparative Example 3, the amount is increased to 5 g. Too much modified glass fiber may be unevenly dispersed in the concrete, affecting the uniformity of the overall structure, resulting in a compressive strength of 5.20 MPa and a crack resistance of 4.00 kN, both lower than those of Examples 1-3.

[0067] In summary, through the analysis of the performance test results of each embodiment and comparative example, it is fully verified that the present application can significantly improve the compressive strength and crack resistance of aerated concrete by modifying the glass fiber, as well as a reasonable raw material ratio and preparation process.

[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A glass fiber reinforced aerated concrete, characterized in that: The raw materials include the following components: 20-30 parts of cement; 10-20 parts of fly ash; 15-25 parts of quicklime; 30-40 parts of silica sand; Aluminum powder 0.1-0.3 parts; 0.5-1.5 parts of foaming agent; Foam stabilizer 0.5-1 part; 1-3 parts of modified glass fiber; 25-35 parts water; The modified glass fiber is obtained by forming an ordered nano composite layer on the surface of the glass fiber through molecular self-assembly of nano titanium dioxide particles.

2. The glass fiber reinforced aerated concrete according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: A. Tetrabutyl titanate was added dropwise into anhydrous ethanol and mixed under magnetic stirring to form solution A; B. Mix deionized water, anhydrous ethanol and glacial acetic acid to form solution B, take solution A and solution B at a volume ratio of 1:1, and add solution B dropwise to solution A under stirring conditions. The dropping speed is controlled at 1 drop / second. After the dropping is completed, continue stirring and reacting for 1-3 hours to obtain a nano titanium dioxide sol; C. Aging, drying and calcining the nano-titanium dioxide sol to obtain nano-titanium dioxide particles; D. Adding nano-titanium dioxide particles to a toluene solution containing 3-aminopropyltrimethoxysilane, wherein the concentration of 3-aminopropyltrimethoxysilane is 0.1-0.3 mol / L, and reacting under reflux at 80° C. for 4-6 hours. After the reaction, washing with anhydrous ethanol, centrifuging, and drying to obtain amino-grafted nano-titanium dioxide particles; E. Sodium dodecyl sulfate, amino-grafted nano-titanium dioxide particles and aluminum triisopropoxide are mixed to obtain a reaction solution, and then the pH value of the reaction solution is adjusted to 6.5 with a dilute hydrochloric acid solution, and then glass fiber is added, and then the reaction is stirred at 40-50° C. and a speed of 200 r / min for 3-5 hours to obtain modified glass fiber.

3. The glass fiber reinforced aerated concrete according to claim 2, characterized in that: In the step A, the volume ratio of tetrabutyl titanate to anhydrous ethanol is 1:(3-5).

4. The glass fiber reinforced aerated concrete according to claim 2, characterized in that: In step B, the volume ratio of deionized water, anhydrous ethanol and glacial acetic acid is 5:(4-6):

2.

5. The glass fiber reinforced aerated concrete according to claim 2, characterized in that: In the step D, the mass ratio of the nano-titanium dioxide particles to the toluene solution containing 3-aminopropyltrimethoxysilane is 1:(3-5).

6. The glass fiber reinforced aerated concrete according to claim 5, characterized in that: In the step D, the mass ratio of the nano-titanium dioxide particles to the toluene solution containing 3-aminopropyltrimethoxysilane is preferably 1:

4.

7. The glass fiber reinforced aerated concrete according to claim 2, characterized in that: In the step E, the mass ratio of sodium dodecyl sulfate, amino-grafted nano titanium dioxide particles and aluminum triisopropoxide is 5:10:

3.

8. The glass fiber reinforced aerated concrete according to claim 1, characterized in that: The foaming agent is any one of hydrogen peroxide, azodicarbonamide and sodium bicarbonate.

9. The glass fiber reinforced aerated concrete according to claim 1, characterized in that: The foam stabilizer is any one of calcium stearate, sodium dodecylbenzene sulfonate and polyvinyl alcohol.

10. A method for preparing glass fiber reinforced aerated concrete according to any one of claims 1 to 9, characterized in that: The steps include: S1. Mix the modified glass fiber with water and stir at a speed of 200 r / min for 3-5 min to obtain a fiber suspension; S2. Add cement, fly ash, quicklime, silica sand, aluminum powder, foaming agent and foam stabilizer into a mixer and stir for 3-5 minutes. Then add the fiber suspension and continue stirring for 10-15 minutes to obtain a uniform slurry. The stirring speed is 200r / min. S3. The slurry is injected into a mold and foamed at a temperature of 40-50° C. for 3-5 hours. The slurry is stirred every 30 minutes during the foaming process. After the foaming is completed, the slurry is cured to obtain glass fiber reinforced aerated concrete.

Citation Information

Patent Citations

  • A kind of lightweight autoclaved aerated concrete and its preparation method

    CN104557107B

  • Glass fiber autoclaved aerated concrete block and preparation method thereof

    CN107673670A

  • High-strength modified synthetic fiber reinforced reactive powder concrete

    CN111233383A

  • Reactive powder concrete and preparation method thereof

    CN112608113A

  • Zirconium silicate composite ceramic roller and preparation method thereof

    CN113788691A